Enhancement of Delignification and Glucan Content of Sugarcane Bagasse by Alkali Pretreatment for Bioethanol Production - Kyaw Wunna; Kiohiko Nakasaki; Joseph Auresenia; Leonila Abella; Peg-asa Gaspilo (Department of Chemical Engineering, Universitas Gadjah Mada, 2021)
The current work aimed to enhance the delignification of sugarcane bagasse (SCB) for bioethanol production. The optimization of alkali (sodium hydroxide) pretreatment parameters such as concentration and residence time was carried out by the Taguchi method using L16 orthogonal array with two factors and four levels. Sugarcane bagasse powder was mixed with sodium hydroxide (NaOH) solution (0.5-2 wt.%) and heated in an autoclave at 121°C and at varied times (30-120 min). From the statistical analysis of data, it was observed that delignification and glucan increased with the increased concentration and short time. The optimum parameters of NaOH pretreatment were 2 wt.% of NaOH concentration and 30 minutes of residence time. At the optimum conditions, 86.8% delignification and 46.6% glucan content of SCB were obtained. Thus, alkali pretreatment optimized by Taguchi design is the effective method to remove lignin and to increase cellulose or glucan content in sugarcane bagasse for facilitating the further catalytic hydrolysis in bioethanol production.